Magnetoelectric polymer-based nanocomposites with magnetically controlled antimicrobial activity - Fernandes, Margarida (2021)
The emergence of antimicrobial resistance is considered a public health problem due to the overuse and misuse of antibiotics which are losing efficacy toward an increasing number of microorganisms. Advanced antimicrobial strategies via development of alternative drugs and materials able to control microbial infections, especially in clinical settings, are urgently needed. In this work, nanocomposite films were developed from the piezoelectric polyvinylidene fluoride (PVDF) polymer, filled with nickel nanowires (NiNws) in an attempt to control and enhance the antimicrobial activity of the materials via applying a magnetic stimulus. The material was achieved through crystallization of PVDF in the electroactive -phase upon incorporation of anisotropic and negatively charged NiNws in the polymeric matrix at a concentration of 1.5 wt %. The nanocomposites have shown to possess certain antimicrobial properties, which could be considerably boosted through the application of a magnetic field. In fact, more than 55% of bacterial growth inhibition was obtained by employing controlled dynamic magnetic conditions for representative Gram-positive and Gram-negative bacteria, compared to only 25% inhibition obtained under static conditions, i.e., without magnetic stimuli application, with the antibiofilm activity clearly improved as well upon dynamic conditions. This work demonstrates a proof-of-concept for materials able to boost on demand their antimicrobial activity and opens the room for applications in novel medical devices with improved control of healthcare-associated infections.